DIFFICULTIES IN ARTICULATION OF SOME CONSONANT SOUNDS: On the material of the English and Georgian languages - Kuparadze, Gia (Online Journal of Humanities ETAGTSU, 2017)
Representatives of small nations today than ever before are "doomed" to multilingualism. Thus, comparative studies can largely simplify foreign language learners’ task to overcome the difficulties, they may face in L2, L3, Lx language acquisition process. The present paper deals with the comparative analysis of the difficulties in articulation of some consonant sounds in English on the one hand and a typologically different language, such as Georgian on the other. The Georgian language is an agglutinative language. Therefore, it is characterized by the root flexion which also reveals the peculiarities of its phonemic system. The study of sounds- despite their simple structure – is accompanied by special difficulties in the foreign language teaching. According to psychology and physiology, interferences of pronunciation in the given field, in terms of foreign “accent”, are the most difficult to eliminate. Finally, in the paper, a special attention is drawn to a discussion how to conduct a didactic analysis of sound contrasts. Full Text (PDF)